ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS 2 MAS AL-MUSTAQIM - Sari, Novita; Rosyid, Rustiyarso; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study entitled " Student Learning Interest Analysis on the Subjects of Sociology Class XI IPS 2 MAS Al-Mustaqim Arang Limbung". A common problem in this study is how to students interest on the subjects of Sociology class XI IPS 2 MAS Al-Mustaqim?. With the sub-problems : (1) How do the feelings of love to students in following the process learning of sociology? (2) How the student's attention at a time when the process learning of sociology?(3) How student involvement in the learning process of sociology?. The purpose of this research is to know the taste of pleasure, attention and involvement of students in the subjects of sociology. This research uses descriptive qualitative approach method. As for the sources data are the students of Class XI 2 IPS that add up to 30 people. Engineering data collection is observation, interview and documentation. Data collecting tool guidance interviews, observation and documentation guidelines. Technique of data analysis in this research include reduction of the data, the presentation of data and verification. Research results is : (1) there is no feeling of love to the students on the subjects of sociology, because students always feel bored when learning takes place. (2) the student's Attention is still less, as there are students were sleeping at the time the teacher explains material (3) student involvement is also less, because students do not contribute actively in the discussion. Keywords: Learning Interest,  Sociology Lesson